Intellectuels iraniens de l'entre-deux-guerres - Yann Richard (Revue des Mondes Musulmans et de la Méditerranée)
The Pahlavi dynasty, which began in 1925, brought Iran into the new era of intensive modernisation and secularisation, a movement which began with the coup d'État in February 1921. In Qom, the clergy reorganised itself from 1922 on. This is when Khomeyni carried out his theological studies. Reformist movements developed in Shi'ite schools at this time, a movement linked to the weakening of traditional centres of Duodeciman Shi'ism in Iraq after the establishment of the Mandate. Religious milieux were sensitive to Muslim reformism in the neighbouring Arab countries. In particular, one can note a strong Salafi influence on Shari'at Sangalajî, a theologian who died in 1944. Censorship quickly became stifling for intellectuals though some continued to serve the new regime. The University of Teheran, created in 1934, constitutes a new departure towards modernity which served to mobilise the educated. Literature, however, heavily influenced by European tendencies, in poetry as well as in prose, found itself in the face of numerous obstacles supported by traditional society and political power.